DEVELOPMENT OF PROFESSIONAL SKILLS OF STUDENTS IN EXTRA-CURRICULAR COURSES - Ibragimova Maryamkhan Gulomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The main goal of guiding students to a profession is to help young people to choose a profession, taking into account their abilities, interests and inclinations, as well as social needs, to determine their life path correctly. Emphasis is placed on the employment of activities and conditions in which each person can fully express his abilities and work with high efficiency.